2013
DOI: 10.1002/trtr.1213
|View full text |Cite
|
Sign up to set email alerts
|

Close Readings and Children's Literature

Abstract: The concept of close reading is an important consideration when addressing the Common Core State Standards. In addition, close reading permeates the CCSS and suggests a particular way of reading and responding to texts. Trying to help students become successful readers in both school based settings and in the world outside of school is still our primary goal as reading teachers. We need to develop our own understandings of the requirements for close reading in various contexts, be ready to demonstrate to our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Over the past decade, practitioners and researchers have reshaped the teaching of close reading to acknowledge that readers make meaning not just within the four corners of the text but also through other factors such as prior linguistic and text experiences as well as the sociocultural context (Fisher & Frey, 2012; Serafini, 2013/2014). Recognizing that close reading requires an interaction between readers and texts, Lehman and Roberts (2013) advocate for a model of close reading that encourages the use of lenses of analysis.…”
Section: Close Reading and Critical Literacymentioning
confidence: 99%
“…Over the past decade, practitioners and researchers have reshaped the teaching of close reading to acknowledge that readers make meaning not just within the four corners of the text but also through other factors such as prior linguistic and text experiences as well as the sociocultural context (Fisher & Frey, 2012; Serafini, 2013/2014). Recognizing that close reading requires an interaction between readers and texts, Lehman and Roberts (2013) advocate for a model of close reading that encourages the use of lenses of analysis.…”
Section: Close Reading and Critical Literacymentioning
confidence: 99%
“…In terms of text processing we focus on e.g. attention (Serafini, 2013a;2013b), motivation (Gambrell, 2011;Roeschl-Heils, Schneider, Kraayenoord, 2003), the ability to solve problems (Braselton & Decker, 1994) or a scope of cognitive effort exerted in processing (Maki, Foley, Kojer, Thompson, & Willert, 1990). The study in the field of research reading with comprehension and metacognition bring rather consistent conclusions: metacognition plays a significant part in the quality of comprehenstion (Bransford, Brown, & Cocking, 2000).…”
Section: Metacognitive Monitoring As a Theoretical And Empirical Consmentioning
confidence: 99%
“…For reading instruction, strategies such as close reading help students develop deeper meaning of words while using evidence from a given text to support student responses. Many researchers (Brown & Kappes, 2012;Dalton, 2013;Serafini, 2013;Roskos & Neuman, 2014) describe close reading as text analysis where rereading of the text is expected. Serafini (2013) suggested that prior to CCSS, teachers were more focused on students' personal responses to a reading instead of challenging students to analyze and understand more complex texts.…”
mentioning
confidence: 99%
“…Many researchers (Brown & Kappes, 2012;Dalton, 2013;Serafini, 2013;Roskos & Neuman, 2014) describe close reading as text analysis where rereading of the text is expected. Serafini (2013) suggested that prior to CCSS, teachers were more focused on students' personal responses to a reading instead of challenging students to analyze and understand more complex texts. Reading strategies like close reading serve a valuable purpose, but may leave some students that are struggling readers or simply disengaged in reading instruction with little motivation to read, especially if the given text is either too difficult to independently read or on a topic that does not interest the student (Malloy, Marinak, Gambrell, & Mazzoni, 2013).…”
mentioning
confidence: 99%